A bundle adjustment solution for a personal computer environment - Rommelaere, C L M (Division of Geomatics, 2026)
Photogrammetry is the science and art of using and measuring photographs for various purposes. The word photogrammetry literally means the measuring of something "written" with light. Various photogrammetric techniques have been developed to solve a wide variety of problems in many fields of endeavour. The bundle solution is one technique which has proven very useful and versatile.